Pathways to urban sustainability : the Atlanta metropolitan region, summary of a workshop - Vollmer, Derek (Sustainability science and technology., 2011)
"The U.S. population is more than 80 percent urban. Recognizing that many metropolitan areas in the United States have been experimenting with various approaches to sustainability, and that despite the differences among regions, there are likely some core similarities and transferable knowledge, Roundtable members selected the metropolitan Atlanta, Georgia region as a case study. The Atlanta region provided a compelling example for exploring urban sustainability issues because of the region's rapid growth rate, well-documented challenges with water, land use, and transportation; and its level of engagement with federal government agencies on matters related to sustainability. Pathways to Urban Sustainability: Lessons from the Atlanta Metropolitan Region: Summary of a Workshop explores the Atlanta region's approach to urban sustainability, with an emphasis on building evidence based foundation upon which policies and programs might be developed. The two day workshop held on September 30 and October 1, 2010 examined how the interaction of various systems (natural and human systems; energy, water and transportations systems) affect the region's social, economic, and environmental conditions. The intent of this workshop summary is to analyze a metropolitan region so that researchers and practitioners can improve their understanding of the spatial and temporal aspects of urban sustainability."--Publisher's description